2019
DOI: 10.1002/jcp.28043
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of CRISP3 predicts a favorable prognosis in patients with mammary carcinoma

Abstract: The discovery of cysteine‐rich secretory protein 3 (CRISP3) has been made in human neutrophils for the first time. Cloning of the complementary DNA (cDNA) for CRISP3 was performed from a cDNA library of human bone marrow. In patients with mammary carcinoma, we found that lower expression of CRISP3 was connected to a significantly improved DFS (disease‐free survival) and OS (overall survival). Furthermore, the CRISP3 protein level was significantly associated with negative ANXA1 protein level. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…LYVE1, CST3, and NCAM1 are also reportedly involved in placental vascular remodeling (Pawlak et al, 2019;Song et al, 2010;Zhang, Xu & Han, 2019). GRN, CD5L, ENO1, CHL1, CRISP3, VASN, and TNIK promote the invasive ability of tumor cells (Aran et al, 2018;Bhandari et al, 2019;Buhusi et al, 2003;Chon et al, 2016;Song et al, 2014;Voshtani et al, 2019;Wang et al, 2019). By contrast, SEMA4B, KRT1, KRT9, FBLN1, and PTGDS are involved in the anti-invasive activity of tumor cells (Blanckaert et al, 2015;Jian et al, 2015;Marano et al, 2018;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…LYVE1, CST3, and NCAM1 are also reportedly involved in placental vascular remodeling (Pawlak et al, 2019;Song et al, 2010;Zhang, Xu & Han, 2019). GRN, CD5L, ENO1, CHL1, CRISP3, VASN, and TNIK promote the invasive ability of tumor cells (Aran et al, 2018;Bhandari et al, 2019;Buhusi et al, 2003;Chon et al, 2016;Song et al, 2014;Voshtani et al, 2019;Wang et al, 2019). By contrast, SEMA4B, KRT1, KRT9, FBLN1, and PTGDS are involved in the anti-invasive activity of tumor cells (Blanckaert et al, 2015;Jian et al, 2015;Marano et al, 2018;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, in the present work, LYZ was identified in the serum of BC patients with the LA subtype, as cysteine-rich secretory protein 3 (CRISP-3) that develops a role in innate immune defense [ 70 ]. Recently, lower expression of CRISP3 was associated with an improved DFS (disease-free survival) and OS (overall survival) in patients with mammary carcinoma [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a member of the cysteine-rich secretory protein (CRISP) family, CRISP3 is expressed in a biased manner in the salivary glands, bone marrow, and esophagus. Previous reports clearly indicate [ 33 , 34 ] that the expression of CRISP3 in prostate carcinoma and mammary carcinoma is obviously upregulated. Marianna Volpert et al [ 33 ] found that CRISP3 expression drives the invasion and progression of prostate cancer.…”
Section: Discussion Of the Top 10 Dysregulated Genes In Osccmentioning
confidence: 97%